Evaluation of Some Selected Agronomic Characters on Yield of Chilli Cultivars/Lines Using Analysis of Covariance - Masood, M Asif; Khokhar, Khalid Mahmood; Raza, Irum (Bangladesh Journal of Agricultural Research, 2012)
The study was carried out to see the effect of some agronomic variables on yield of chilli cultivars/lines using covariance analysis technique. Data were recorded for yield and other six agronomic variables, namely time to flowering (days), time to maturity (days), fruit weight per plant in grams, average fruit weight in grams, fruit width in centimeters, and fruit length in centimeters. Among six agronomic variables, fruit weight per plant (grams) is highly significant and linearly related to the plant yield having value of correlation coefficient (r) 0.99 whereas average fruit weight (grams) was significant at 5 percent and linearly related to the yield having correlation coefficient value 0.55. Analysis of variance (ANOVA) and analysis of covariance (ANCOVA) were run by taking fruit weight per plant (grams) as covariate. The error mean square (EMS) without covariate was 1.344 under ANOVA, while error mean square was 0.007 under ANCOVA with covariate. The results depicted that use of covariate reduced error mean square in ANCOVA. It indicated that ANCOVA is more efficient than ANOVA for improving the results of the experiment. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11233 Bangladesh J. Agril. Res. 37(2): 301-306, June 2012